2016
DOI: 10.1371/journal.pone.0154981
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosation and Nitration of Fulvic Acid, Peat and Coal with Nitric Acid

Abstract: Nitrohumic acids, produced from base extraction of coals and peats oxidized with nitric acid, have received considerable attention as soil ammendments in agriculture. The nitration chemistry however is incompletely understood. Moreover, there is a need to understand the reaction of nitric acid with natural organic matter (NOM) in general, in the context of a variety of environmental and biogeochemical processes. Suwannee River NOM, Suwannee River fulvic acid, and Pahokee Peat fulvic acid were treated with 15N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Shi et al (2012) showed that HNO 3 pre-treatment of coal decreases ash content and aromaticity but increases substrate porosity, oxygenation of aliphatic carbon, and the quantity of humic acid carbon. Also, solid state 15 N NMR spectroscopy has revealed that, in addition to nitro groups from nitration of aromatic carbon, products attributable to nitrosation reactions are evident in coal pre-treated with HNO 3 and, that secondary reaction products of the initially formed oximes are also produced (Thorn and Cox 2016). Although the mechanism underlying coal nitration remains poorly understood, the last step in the oxidation of phenol with nitrous acid regenerates nitrous acid which will continue to react as a nitrosating agent.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2012) showed that HNO 3 pre-treatment of coal decreases ash content and aromaticity but increases substrate porosity, oxygenation of aliphatic carbon, and the quantity of humic acid carbon. Also, solid state 15 N NMR spectroscopy has revealed that, in addition to nitro groups from nitration of aromatic carbon, products attributable to nitrosation reactions are evident in coal pre-treated with HNO 3 and, that secondary reaction products of the initially formed oximes are also produced (Thorn and Cox 2016). Although the mechanism underlying coal nitration remains poorly understood, the last step in the oxidation of phenol with nitrous acid regenerates nitrous acid which will continue to react as a nitrosating agent.…”
Section: Discussionmentioning
confidence: 99%
“…Reported chemical shis for nitrosamine compounds are above 500 ppm on the ammonia scale. 43 Other studies reported for simple symmetrically-substituted nitrosamines NMR shis from À107.2 to À146.7 ppm for N1(-N]O) and from +154.6 to +175.9 ppm for N2(]O), referenced to 15 NO 3 Na. 44 In unsymmetrically substituted nitrosamines N1 resonates respectively from À103.7 to À153.6 ppm, while N2from +157.0 to +176.9 ppm.…”
Section: Chemistrymentioning
confidence: 98%
“…In general, the river samples gave the highest amounts of secondary nitrosation products, while the coal samples gave the least. 82 Nitration of NOM using 15 N-labeled reagents could be of use as a molecular tagging method for structure elucidation, as it is complementary to hydroxyl modifying methods, but greater control over the specificity of the reaction by using alternative reagents would be desirable. A recent review by Liu lists alternatives that could be tried.…”
Section: Hexamethyldisilazane (Hmds)mentioning
confidence: 99%